Integrated Marketing Communication Strategies on Patronage of Hospitality Organisations in Akwa Ibom State - Christiana Archibong (INTERNATIONAL JOURNAL OF PUBLIC RELATIONS AND SOCIAL SCIENCES, 2026)
This study investigates the influence of Integrated Marketing Communication (IMC) strategies on customer patronage of selected hospitality organisations in Akwa Ibom State, Nigeria. The increasing competition within the hospitality sector has necessitated the adoption of coordinated marketing communication strategies that ensure consistency and effectiveness in reaching target audiences. IMC integrates advertising, sales promotion, public relations, and direct marketing to deliver a unified brand message across multiple channels. Despite the widespread adoption of IMC strategies by hospitality firms, concerns remain regarding their effectiveness in influencing customer patronage. This study adopts a survey research design, collecting data from customers of selected hospitality organisations across the three senatorial districts of Akwa Ibom State. Findings reveal that advertising significantly enhances awareness and attracts customers, while sales promotion stimulates immediate purchase decisions through incentives such as discounts and bonus offers. Public relations, on the other hand, plays a crucial role in building trust, credibility, and long-term customer relationships. The study further establishes that the integration of these communication tools leads to improved brand perception and increased customer loyalty. However, challenges such as inadequate marketing budgets, lack of skilled personnel, and poor coordination hinder effective IMC implementation. The study concludes that IMC is a vital strategic tool for enhancing customer patronage in the hospitality industry. It recommends that organisations adopt a holistic and data-driven approach to IMC, ensuring consistency across all communication platforms to maximise impact and achieve sustainable competitive advantage.